Effect of An Ayurvedic Management in Computer Vision Syndrome (International Journal of Ayurveda and Pharma Research, 2023)
Computer Vision Syndrome (CVS) is the new nomenclature to the visual, ocular, and systemic symptoms arising due to the long time and improper working on the computer and is emerging as a pandemic in the 21st century. On critical analysis of the symptoms of CVS, it seems to be a Vata-Pitta ocular cum systemic disease which needs systemic as well as topical treatment approach. Shushkakshipaka is a similar disease explained in Sarvakshigatha roga. The management includes Anutaila nasya and Jeevaneya ghritha tarpana. Hence an attempt is made to study the benefit of this therapy in CVS which is having similarity with Shushkakshipaka. Patients aged 20-50 diagnosed as CVS were selected for the study and 30 eyes were studied. Data was collected by case proforma, clinical examination and investigations such as Visual analysis, Schirmer’s test, Tear break up time test. Then they were subjected to Deepana- Pachana, Snehana with Jeevaneya gritha, Swedana, Kayasodhana as Virechana with Gandharva eranda taila, Marsa nasya with Anutaila, Tharpana with Jeevaneya gritha and Putapaka with Jeevaneya puatapaka rasa. During the analysis of the distribution of symptoms there was significant improvement noted which sustained during follow up period also. Nasya gives Bala to Uttamanga thus preventing Stanasamsraya due to Kha vaigunya. Here Vicharana snehapana with Jeevaneya gana gritha and Tarpana with the same is done along with Anutaila nasya. Jeevaneya gritha is used for the Snehana karma and nourishes the eyes. Gritha itself is Vatapitta sama and helps to reduce the symptoms which are Vatapitta in nature.